Lanthanide-doped aluminate phosphors : synthesis, properties, and applications /: synthesis, properties, and applications. (2023) - Yerpude, Atul; Pawade, Vijay B; Dhoble, Sanjay J, 1967-; Koao, Lehlohonolo Fortune
No abstract available